Epoxide ring-opening reaction by using sol-gel-synthesized palladium supported on a strontium hydroxyl fluoride catalyst - Acham, Vaibhav R.; Dongare, Mohan K.; Kemnitz, Erhard; Umbarkar, Shubhangi B. (Comptes Rendus Chimie, 2016)
Palladium supported on a strontium hydroxyl fluoride catalyst was synthesized by a one-pot fluorolytic sol-gel method. The prepared catalyst was characterized by various physicochemical techniques. The sol-gel method has led to the formation of a high surface area (57 m(2)g(-1)), mesoporous (pore diameter = 13.0 nm) catalyst with uniform dispersion of Pd nanoparticles of size similar to 7 nm on the surface of strontium hydroxyl fluoride. The catalyst was used for epoxide alcoholysis, and 100% conversion was obtained with 96% selectivity for beta-alkoxy alcohols under mild conditions: The catalyst could be recycled for up to three catalytic cycles without any appreciable decrease in conversion and selectivity, indicating the stability of the catalyst under the reaction conditions. Further, the mechanism of alcoholysis was proposed on the basis of the physicochemical characteristics of the catalyst and on the basis of the products formed during the catalytic reaction. (C) 2016 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.

Environmentally benign bioderived carbon microspheres-supported molybdena nanoparticles as catalyst for the epoxidation reaction - Doke, Dhananjay S.; Umbarkar, Shubhangi B.; Gawande, Manoj B.; Zbori, Radek; Biradar, Ankush V. (ACS Sustainable Chemistry & Engineering, 2017)
A one pot synthesis of molybdenum oxide nanoparticles (NPs supported on bioderived carbon microspheres is reported. The catalyst was synthesized by the low temperature hydrothermal (LTH) method using D-glucose and bagasse as the carbon source. The carbonization of bagasse resulted in the formation of nonuniform carbon microspheres while glucose resulted in uniform carbon spheres. SEM and STEM elemental mapping show the uniform distribution of molybdenum oxide NPs over the carbon microspheres. XPS spectroscopy confirmed that molybdenum was in the Mo6+ oxidation state. The 1% MoO3 supported on carbon microspheres derived from D-glucose showed excellent catalytic activity up to 100% olefin conversion with 100% epoxide selectivity using organic tent-butyl hydroperoxide as an oxidant. The catalyst was successfully used for up to five cycles without losing substantial activity and selectivity.
Keywords: Carbon microspheres; epoxidation; heterogeneous catalysis; Hydrothermal synthesis; TBHP

Enhancement of mechanical and rheological properties of PA-12 through silane modification - Jadhav, V. Pravin; Mahajan, Digvijay; Patil, Prashant; Umbarkar, Shubhangi B.; Pol, Harshawardhan (Bulletin of Materials Science, 2025)
This research examines the effects of silane modifications on polyamide 12 (PA-12) to improve its mechanical and thermal properties. The study employs a reactive extrusion technique to integrate various silanes-Dynasylan (R) AMEO, Dynasylan (R) 1189, Dynasylan (R) DAMO and Dynasylan (R) VPS 4721-at different concentrations (0.25, 0.5 and 0.75%). Key findings reveal that silane modifications significantly enhance the tensile strength, impact resistance and viscoelastic behaviour of PA-12, with the Dynasylan (R) DAMO formulation achieving the highest tensile strength of 38.25 MPa vis-& agrave;-vis 8.02 MPa for PA-12. The modifications also resulted in a reduction of crystallinity by over 35%, contributing to improved toughness and impact strength. Rheological assessments indicate that the flow properties of PA-12 are positively altered, enhancing its complex viscosity and storage modulus, which are crucial for applications in automotive and aerospace industries. Thermal analysis through differential scanning calorimetry and thermogravimetric analysis confirms improved thermal stability, particularly in the 0.5% Dynasylan (R) AMEO-modified sample, exhibiting an onset temperature of 421.87 degrees C. The study emphasizes the importance of the silane type and dosage in tailoring PA-12's performance for advanced applications, suggesting future research directions to further refine silane-modification techniques for enhanced polymer performance. This research provides valuable insights into polymer-modification strategies, highlighting the potential for silane treatments to optimize the mechanical, thermal and rheological properties of PA-12 for diverse industrial applications.
Keywords: mechanical properties; Polyamide 12 (PA-12); reactive extrusion; rheological behaviour; silane modification; thermal stability